A Scientometric Review on Rockburst in Hard Rock: Two Decades of Review from 2000 to 2019. (30th April 2020) - Liang, Weizhang; Dai, Bing; Zhao, Guoyan; Wu, Hao
Abstract : Considerable advances have been made from diverse perspectives in rockburst research to guarantee the safety of deep underground activities. However, to date, few reviews have been made to systematically analyze the overall research status of rockburst. This study is aimed at providing a scientometric review on rockburst research in hard rock from 2000 to 2019. First, a total of 430 papers were collected from the Web of Science Core Collection database. Then, the CiteSpace software was adopted to conduct a scientometric analysis from five main aspects. Finally, the existing knowledge domains and future directions were discussed. Based on the results of this study, main countries, institutions, authors, and journals of rockburst research were revealed, and some important papers, hot topics, and evolutionary trends were found out. This review contributes to the integrated knowledge map of rockburst research in hard rock and provides researchers a valuable and in-depth understanding in this domain.